Analysis of Staff with Excellent Performance at the Central General Hospital of the Eastern Region (Benchmarking Analysis: Performance Accountability Report of Government Agencies of Dr. Wahidin Sudirohusodo General Hospital Makassar and Dr. Johannes Leimena General Hospital Ambon 2021-2023) - Rahaded, Aisa Barkah; Ruliyandari, Rochana (Jurnal Kesehatan Masyarakat Perkotaan, 2025)
Background: The increasingly fierce level of competition makes an organization must have good performance. This is based on the 2021-2023 Government Agency Performance Accountability Report (LAKIP) which has key performance indicators (KPIs) for excellent performance on hospital staff. So that Dr. Johannes Leimena Ambon Hospital became motivated by RSUP. Dr. Wahidin Sudirohusodo Makassar so that both contribute to the vertical Technical Implementation Unit Hospital (UPT Hospital) in Eastern Indonesia. Research Methods: Literature research by conducting a bencmarking analysis method at RSUP. Dr. Wahidin Sudirohusodo Makassar and Dr. Johannes Leimena Ambon Hospital based on LAKIP 2021-2023. Results and Discussion: The achievement of staff indicators with excellent performance can exceed the target every year at Dr. Wahidin Sudirohusodo Hospital, while Dr. Johannes Leimena Ambon Hospital has not been able to measure staff indicators with excellent performance in 2021. Therefore, there is planning for resource efficiency by providing education and training, placing staff according to their competence, and the importance of support or motivation provided by the hospital for its employees. Conclusion: Dr. Wahidin Sudirohusodo Hospital Makassar and Dr. Johannes Leimena Hospital Ambon can exceed the target achievement of staff with excellent performance in 2022. However, in 2023, there was a change in the Business Strategic Plan for the implementation of KPIs.